ANALISE DE CUSTO-EFETIVIDADE DO COMPONENTE DE LEISHMANIOSE NO PROJETO DE CONTROLE DE DOENÇAS ENDÊMICAS NO NORDESTE DO BRASIL - Akhavan, Dariush (Revista de Patologia Tropical / Journal of Tropical Pathology, 2012)
ANALYSIS OF THE COST-EFFECTIVENESS OF THE LEISHMANIASIS COMPONENT OF THE PROJECT FOR THE CONTROL OF ENDEMIC DIASEASES IN THE NORTHEAST (PCDEN) OF BRAZIL.